Parents’ Perceptions of English Language Teaching in Early Childhood: A Case Study of Kindergartens in Probolinggo - Indah Dwi Lestari; Rian Sri Rahayu (English Teaching and Linguistics Journal (ETLiJ), 2026)
The growing emphasis on English language teaching in early childhood has increased parents’awareness of its potential contribution to children’s future language development. This study aims to explore parents’ perseptions of English language teaching in kindergartens in Probolinggo, East Java, and to examine the role of parental support in children’s early English learning. A qualitative approach was employed through semi-structured interviews with five parents of children aged four to six years, consisting of two fathers and three mothers, supported by one additional informant who was a doctoral student and parent of a four-year-old child. The interview data were analyzed using thematic analysis to identify recurring patterns and themes. The findings indicate thet parents perceive English as an important global language and strongly support its introduction from an early age. They believe that early English lerning contributes to children’s language development, self-confidence, and future educational and career opportunities. Parents also recognize that active involvement at home through daily communication and continous encouragement plays a crucial role in reinforcing children’s learning experiences. These findings highlight the importance of collaboration between schools and families in vreating meaningful early English learning environments and provide practical insights for educators and policymakers in designing parent-inclusive language education programs.